CLASS TALK SHOW TO TEACH SPEAKING DIALOGUE - Wisudawaty, Umi; ., Sudarsono; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Â Abstract: The purpose of this research is to find out the level of the effectiveness of class talk show to teach speaking dialogue to Year-8 students of â€œSMP Negeri 3 Pontianakâ€ in Academic Year 2014/2015. This research was a quasi experimental research with non-equivalent control group design. The sampling technique was a cluster random sampling. The samples were Class VIII C as the experimental group and Class VIII D as the control group. The data were collected by applying the pre-test and the post-test. Then the data were analyzed by using Effect Size (ES) formula. The research finding shows that the effect size of the treatment is 2.09 (Ëƒ1.00). It is categorised â€œstrongâ€. It indicates that class talk show is highly-effective to teach speaking dialogue to Year-8 students. Key words: Class talk show, speaking dialogue. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifan class talk show dalam pengajaran berbicara dialog kepada siswa kelas 8 SMP Negeri 3 Pontianak tahun ajaran 2014/2015. Penelitian ini adalah sebuah penelitian quasi experimental dengan rancangan non-equivalent control group. Teknik sampel yang digunakan adalah cluster random sampling. Sampel dalam penelitian ini adalah kelas VIII C sebagai kelompok experimental dan kelas VIII D sebagai kelompok kontrol. Data-data diambil dengan menerapkan pre-test dan post-test. Kemudian data dianalisis dengan menggunakan rumus ES (tingkat efektifitas). Hasil penelitian menunjukkan bahwa efek dari penggunaan class talk show adalah 2.09 (>1.00). Hasil ini dikategorikan memiliki efek yang kuat. Â Hal ini menandakan bahwa class talk show sangat efektif dalam pengajaran berbicara dialog kepada siswa kelas 8. Â Kata kunci: Class talk show,berbicara dialog.